The psychoanalytic study of lives over time : clinical and research perspectives on children who return to treatment in adulthood - Cohen, Jonathan, Ph. D.; Cohler, Bertram J. (Practical resources for the mental health professional., 2000)
The Psychoanalytic Study of Lives Over Time: Clinical and Research Perspectives on Children Who Return to Treatment in Adulthood is a landmark volume that addresses an essential clinical question: what is the nature of the process and outcome of clinical work with children? An internationally renowned group of analytic clinicians and clinician-researchers all comment on three fascinating child analytic situations where the patient returned to treatment in adulthood.